Identifying a consensus sample type to test for Chlamydia trachomatis, Neisseria gonorrhoeae, Mycoplasma genitalium, Trichomonas vaginalis and human papillomavirus. (December 2018) - Coorevits, L.; Traen, A.; Bingé, L.; Van Dorpe, J.; Praet, M.; Boelens, J.; Padalko, E.
Abstract: Objectives: Sexually transmitted infections (STIs) are a global cause of acute illness. Early detection plays a crucial role in interrupting transmission and preventing complications. However, the accessibility of STI testing is curbed by the lack of an overall preferred sample type. By means of a prospective study in female sex workers (FSW), we compared the sensitivity of samples from different anatomical sites in detecting Neisseria gonorrhoeae, Chlamydia trachomatis, Trichomonas vaginalis, Mycoplasma genitalium and human papillomavirus. Besides, we documented the prevalence of each STI in this high-risk population. Methods: We selected 303 FSW and tested them for each STI by nucleic acid amplification testing on two vaginal and cervical swabs from different manufacturers, cervical smear and first-void urine. The sensitivity of each sample type was compared for each infectious agent in order to identify a consensus sample type. Results: Vaginal swabs were superior to all other sample types, with an overall sensitivity of 86%. The sensitivity was the lowest for first-void urine, detecting only 63% of positive cases. The prevalence was 3.3% (10/299) for Neisseria gonorrhoeae ; 9.0% (27/299) for Chlamydia trachomatis ; 7.4% (22/298) for Trichomonas vaginalis ; 10.8% (32/296) for Mycoplasma genitalium and 55.6% (158/284) for human papillomavirus. Conclusions: When testing for STIs, vaginal swabs are the sample of choice and first-void urine should be avoided. Designating (self-sampled) vaginal swabs as a consensus sample type enables harmonization of STI testing and extension of testing to large numbers of unscreened females.